ANALYSIS OF STUDENTS’ THINKING SKILLS IN BIOLOGY LEARNING: STUDY AT A SCHOOL IN PADANG, INDONESIA - Rosalia, Restia; Amri, Erismar; Maharani, Ade Dewi (JURNAL PENA SAINS, 2024)
There are several skills used to face the challenges of 21st century development which are abbreviated as 4C, namely critical thinking, collaboration, creativity and communication skills. The concept of 21st century learning, in its development, provides global challenges to the current generation that is developing and this needs to be considered. However, those 21st century skills have not been fully implemented in the learning process, especially in the senior high schools in Padang. The purpose of this study was to determine the 21st Century Skills of Class XII MIPA Students in Biology Learning at Adabiah Padang Private High School. This type of research is descriptive research. The population was all class XII MIPA students at Adabiah Padang Private High School totaling 162 students. The sample taken was 40 students using random sampling technique. The instrument used in collecting data in this study was a test in the form of multiple-choice objectives totaling 17 questions to assess critical thinking skills and observation sheets for creativity, collaboration and communication. The questions used in this study were questions that had been tested for validity and reliability. The results showed that the value of 21st century skills of class XII MIPA students at Adabiah Padang Private High School was 69.57 with high criteria. In detail, students' 21st century skills in critical thinking skills, creativity, collaboration and communication were respectively 73.21; 65.10; 69.64 and 70.31 with high criteria. Therefore, it can be concluded that students' 21st Century skills in biology learning at Adabiah Padang Private High School with high criteria.